Resident evil [videorecording (DVD)] - Anderson, Paul, 1965- (Screen Gems ; Columbia TriStar Home Entertainment, 2004)
A virus has escaped and infected a secret lab and the scientists turned into zombies. A special-operations force is sent to battle the virus before it infects the planet.